HeartMate 3 left ventricular assist system implantation technique: the devil is in the detail. (26th September 2018) - Netuka, Ivan
Abstract: Surgical nuances of the implantation procedure of the HeartMate 3 left ventricular assist system (Abbott Corp., IL, USA) are discussed in this study. Particular attention is devoted to surgical details, preventative actions and considerations related to alternative implantation strategies. Dedicated surgical implantation tools may ease the implantation experience.